Scientific Approach in Teaching Speaking Used by The English Teacher at SMA Islam Batu - Hilwannahl Rokhyandi; Puji Sumarsono (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2015)
Scientific Approach in Teaching Speaking Used by The English Teacher at SMA Islam Batu